The Implementation of Village Infrastructure Development Policy in Surawangi Village, Jatiwangi District, Majalengka Regency - Baihaqi, Anienda Noor Laila; Khumayah, Siti (Jurnal Polisci, 2025)
Background. Village infrastructure development plays a crucial role in enhancing the welfare of people in rural areas. Adequate infrastructure not only supports economic and social activities but also acts as a foundation for realizing equitable development. Aims. This study aims to analyze the implementation of village infrastructure development policies, especially the construction of village roads, in Surawangi Village, Jatiwangi District, Majalengka Regency. Methods. The research method employed is a descriptive qualitative approach, with a primary focus on George C. Edwards III's policy implementation theory, which encompasses four key variables: communication, resources, disposition, and bureaucratic structure. Result. The study's results indicate that the policy has been implemented, but it faces several obstacles. Policy communication remains suboptimal, particularly in the delivery of technical information. Resources such as tools and materials are readily available; however, limited human resources and technical data pose an obstacle. Conclusion. This study concludes that strengthening communication, capacity building, and bureaucratic reform at the village level are needed to support the implementation of more effective, participatory, and sustainable policies. Implementation. The implementation disposition is quite positive, characterized by high commitment; however, it has not been supported by adequate administrative compliance. A formal bureaucratic structure has been established; however, weaknesses remain in coordination, documentation, and procedural efficiency.